Understanding Organizational Commitment in Public Hospitals: Insights from Work-Life Balance, Perceived Organizational Support, and Job Satisfaction - Syarifahtun Nur Maknunah; Hengky Widhiandono; Fatmah Bagis; Totok Haryanto (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study aims to analyze the influence of work-life balance and perceived organizational support on organizational commitment with job satisfaction as a mediating variable among Civil Servants at Hj. Anna Lasmanah Banjarnegara Regional General Hospital. A quantitative approach was employed using a questionnaire survey distributed to 120 respondents, determined using the Slovin formula (with a 10% margin of error) from a total population of 340 civil servants, selected through simple random sampling. The data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with SmartPLS 4.0. The results show that work-life balance is not significant for organizational commitment but has a significant positive effect on job satisfaction. Perceived organizational support has a considerable positive impact on both organizational commitment and job satisfaction. Furthermore, job satisfaction is shown to mediate the relationships between work-life balance and perceived organizational support, and between perceived organizational support and organizational commitment. This study indicates that organizational commitment among public hospital employees is not solely determined by work–life balance but is more strongly driven by perceived organizational support, which enhances job satisfaction.